The Influence of Self-efficacy on The Relationship Between Depression and HIV-related Stigma with ART Adherence Among The Youth in Malawi - Eric Umar; Judith A Levy; Geri Donenberg; Mary Ellen Mackesy-Amiti; Hening Pujasari; Robert C Bailey (Faculty of Nursing Universitas Indonesia, 2019)
Depression and HIV-related stigma, among other factors, have been inversely linked independently with adherence to antiretroviral therapy (ART) among the youth. However, the processes through which the various factors influence this relationship is not fully known. Guided by Social Action Theory, we examined the interactive mechanisms through which depression, HIV-related stigma, and self-efficacy influenced ART adherence and whether or not these relationships are moderated by gender. A total of 450 HIV-positive youth (13–24 years) in Malawi receiving ART participated in this cross-sectional study. Moderated mediation analyses were conducted using Hayes’ PROCESS macro 2.11 in SPSS. ART adherence was measured by pill count. Findings showed that self-efficacy mediated the effects of depression and stigma on ART adherence. The analyses also revealed that gender moderated both the direct and indirect influence of depression and stigma (via self-efficacy) on ART adherence. Furthermore, self-efficacy simultaneously mediated and moderated the relationship between stigma and ART adherence. The interactive mechanisms through which various factors influence ART nonadherence must be considered to design effective interventions. To reduce the impact of depression and stigma on ART adherence, medication self-efficacy should be bolstered while taking gender in consideration. Keywords: Adolescent, Antiretroviral adherence, Malawi, Moderated mediation, Social action theory, Youth Abstrak Pengaruh Efikasi Diri Terhadap Hubungan antara Depresi dan Stigma HIV dengan Kepatuhan Terapi ART pada Remaja di Malawi. Depresi dan stigma HIV, di antara faktor-faktor lain, berhubungan terbalik secara independen dengan kepatuhan terapi antiretroviral (ART) pada remaja. Akan tetapi, dalam prosesnya faktor yang memengaruhi hubungan ini belum sepenuhnya diketahui. Berdasarkan Teori Perilaku Sosial, penelitian ini dilakukan bertujuan untuk mengkaji mekanisme interaktif depresi, stigma HIV, dan efikasi diri yang memengaruhi kepatuhan ART, dan untuk mengetahui apakah hubungan ini dimoderasi oleh gender atau tidak. Sebanyak 450 remaja dengan HIV-positif (13–24 tahun) di Malawi yang menerima ART ikut berpartisipasi dalam penelitian potong lintang ini. Analisis mediasi moderated dilakukan dengan menggunakan Hayes 'PROCESS macro 2.11 pada SPSS. Kepatuhan ART diukur menggunakan jumlah pil. Hasil penelitian menunjukkan bahwa efikasi diri memediasi efek depresi dan stigma pada kepatuhan ART. Hasil analisis juga mengungkapkan bahwa jenis kelamin memoderasi pengaruh langsung dan tidak langsung dari depresi dan stigma (melalui efikasi diri) terhadap kepatuhan ART. Lebih lanjut,efikasi diri secara bersamaan mediasi dan moderasi hubungan antara stigma dan kepatuhan ART. Mekanisme interaktif dengan berbagai faktor yang memengaruhi ketidakpatuhan ART harus dipertimbangkan untuk merancang intervensi yang efektif. Untuk mengurangi dampak depresi dan stigma terhadap kepatuhan ART, efikasi diri pengobatan harus didukung saat mempertimbangkan jenis kelamin. Kata kunci: Kepatuhan antiretroviral, Malawi, Mediasi tingkat menengah, Teori Perilaku Sosial, Remaja